2010
DOI: 10.3168/jds.2010-3400
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: The application of alkaline phosphatase assays for the validation of milk product pasteurization

Abstract: Standard practices for indirectly assessing the pasteurization status of milk products are primarily based on the thermal inactivation kinetics of the endogenous milk enzyme, alkaline phosphatase (ALP). This assessment provides an invaluable, if not required, tool for both regulatory and in-house process control and validation. Endogenous milk ALP manifests a slightly higher heat resistance than the pathogenic microflora upon which pasteurization time and temperature requirements are based. Hence, ALP activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 71 publications
2
79
1
11
Order By: Relevance
“…Alkaline phosphatase [AP, ALP] (membrane): Alkaline phosphatase is a membrane-bound enzyme that catalyzes specific chemical reactions within the body especially the hydrolysis of a phosphate group from an organic molecule at an alkaline pH [12]. However, if it is present in serum in large amounts, it is diagnostic of bone or liver disease or a tumor in these organs [13].…”
Section: Markers Of Cholestatic Injury Enzymaticmentioning
confidence: 99%
“…Alkaline phosphatase [AP, ALP] (membrane): Alkaline phosphatase is a membrane-bound enzyme that catalyzes specific chemical reactions within the body especially the hydrolysis of a phosphate group from an organic molecule at an alkaline pH [12]. However, if it is present in serum in large amounts, it is diagnostic of bone or liver disease or a tumor in these organs [13].…”
Section: Markers Of Cholestatic Injury Enzymaticmentioning
confidence: 99%
“…ALP can be used in different fields such as immunoassays and electrochemical immunosensors as a labeling enzyme in the dairy industry as an indicator of successful pasteurization, in molecular biology laboratories for preserving DNA molecules, etc. (Muginova et al, 2007;Kreuzer et al, 1999;Rankin et al, 2010;Rittie and Perbal, 2008). Therefore, the improvement of the enzymatic functional stability is important.…”
Section: Introductionmentioning
confidence: 99%
“…It became recognizable when it was confirmed that the requirement for timetemperature relationships to inactivate the ALP required slightly higher as compared to kill Mycobacterium tuberculosis [56,57]. Almost 40% activity of ALP in raw cow milk is declared to be linked with the milk fat globule membrane (MFGM) in the cream phase, though the rest is soluble or dispersed in whey membrane particles (WMP) in skim milk [58].…”
Section: Alkaline Phosphatasementioning
confidence: 91%